Konsep Garapan Tari Manunggal Padi - Aulia, Elda (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The Manugal Padi Dance has the aim of conveying the life of the people of the village of Perigi Talang Nangka, who struggle to survive amidst limited agricultural land. The concept of this dance performance combines movements that reflect the community’s activities when planting rice, which is carried out once a year during the dry season. This depicts the process of people planting rice as a symbol of hard work and togetherness. In this dance work there are four scenes depicting various stages in the farming process, starting from clearing land to closing holes in the ground after planting rice. The performance involves three dancers with traditional make-up and clothing, as well as uses that support the narrative. Through this work, it is hoped that this work can be an inspiration for the younger generation in that works of art through this Garapan concept also convey messages and increase awareness of the importance of preserving local culture and traditions.